Conditional conservatism and reactions of equity investors on management earnings forecasts of firms in Thailand - Bangmek R. (2017)
© 2016, University of Malaya. All rights reserved. Manuscript type: Research paper Research aims: This research tests the contracting efficiency of conservatism by investigating the relationship between conditional conservatism and the reactions of equity investors on management earnings forecast disclosures. Design / Methodology / Approach: The tests were conducted on firms listed in Thailand. Conditional conservatism was measured by using Khan and Watts’ (2009) model. The cumulative market-adjusted abnormal returns approach was used to measure market reactions to management earnings forecast disclosures. Research findings: Findings show that conditional conservatism is positively associated with cumulative excess returns around earnings forecasts release dates. This suggests that conditional conservatism mitigates information asymmetry by committing managers into disclosing credible earnings forecast information. This leads to positive reactions by equity investors. Theoretical contributions / Originality: This paper fulfills an identified need in studying how conservatism enhances the value of voluntary disclosure information and how it influences market reactions to management earnings forecast disclosures. Practitioner / Policy implications: This paper includes implications for the development of disclosure rules for Thai firms and for the improvement of the prudence approach in the conceptual accounting framework.